Extensive growth and growth boundary model for non-proteolytic Clostridium botulinum – Evaluation and validation with MAP and smoked foods. (April 2022) - Koukou, Ioulia; Dahl Devitt, Tina; Dalgaard, Paw
Abstract: The growth inhibiting effect of lactic acid bacteria (LAB) on non-proteolytic Clostridium botulinum was studied. LAB had no significant effect on growth of C. botulinum and their effect was not included in the model to be evaluated. An available cardinal parameter growth and growth boundary model for non-proteolytic C. botulinum (Koukou et al., 2021; https://doi.org/10.1016/j.ijfoodmicro.2021.109162 ) was evaluated using a total of 822 time-to-toxin (TTT) formation data extracted from the scientific literature for seafood, poultry, vegetables and meat products. These data included smoked products and food stored in air, vacuum or modified atmosphere packaging (MAP) with added CO2 . The available extensive model predicted TTT formation without bias (Bf-TTT value = 0.99) and with a reasonable accuracy (Af-TTT value = 1.76). The model was successfully validated for seafood and poultry products. This study substantially increased the range of applicability of the available growth and growth boundary model for non-proteolytic C. botulinum. The performed evaluation showed this model can be used to predict environmental conditions to prevent growth in seafood and poultry products including smoked fish and MAP foods. It is expected that this validated model will contribute to product development and innovation including new sodium reduced foods. Highlights: No significant effect on C. botulinum growth rates by lactic acid bacteria. Model extensively validated using time-to-toxin data (n = 811). Extensive model applicable for seafood, poultry and vegetable products. Predictions included smoked seafood and MAP products.